A two‐dimensional copper(II) coordination polymer based on 2, 4′‐oxybis(benzoate) and 4, 4′‐bipyridine. Issue 7 (9th June 2017) - Tang, Long; Zhang, Juan; Liu, Xiao-Xia; Wang, Ji-Jiang; Fu, Feng
Abstract : This work demonstrates that flexible dicarboxylate ligands can be employed with Cu II ions and linear N, N ′‐donor ligand systems to produce a two‐dimensional wave‐like network coordination polymer. The two‐dimensional layers are expanded into a three‐dimensional supramolecular structure through intermolecular O—H…O and C—H…O hydrogen bonds. Abstract : The reaction of Cu(NO3 )2 ·3H2 O with 2, 4′‐oxybis(benzoic acid) and 4, 4′‐bipyridine under hydrothermal conditions produced a new mixed‐ligand two‐dimensional copper(II) coordination polymer, namely poly[[(μ‐4, 4′‐bipyridine‐κ 2 N, N ′)[μ‐2, 4′‐oxybis(benzoato)‐κ 4 O 2, O 2′ : O 4, O 4′ ]copper(II)] monohydrate], {[Cu(C14 H8 O5 )(C10 H8 N2 )]·H2 O} n, which was characterized by elemental analysis, IR spectroscopy, thermogravimetric analysis and single‐crystal X‐ray diffraction. The X‐ray diffraction crystal structure analysis reveals that the Cu II ions are connected to form a two‐dimensional wave‐like network through 4, 4′‐bipyridine and 2, 4′‐oxybis(benzoate) ligands. The two‐dimensional layers are expanded into a three‐dimensional supramolecular structure through intermolecular O—H…O and C—H…O hydrogen bonds. Furthermore, magnetic susceptibility measurements indicate that the complex shows weak antiferromagnetic interactions between adjacent Cu II ions.